Additive Theories of Rationality: A Critique. (26th January 2016) - Boyle, Matthew
Abstract: Additive theories of rationality, as I use the term, are theories that hold that an account of our capacity to reflect on perceptually‐given reasons for belief and desire‐based reasons for action can begin with an account of what it is to perceive and desire, in terms that do not presuppose any connection to the capacity to reflect on reasons, and then can add an account of the capacity for rational reflection, conceived as an independent capacity to 'monitor' and 'regulate' our believing‐on‐the‐basis‐of‐perception and our acting‐on‐the‐basis‐of‐desire. I show that a number of recent discussions of human rationality are committed to an additive approach, and I raise two difficulties for this approach, each analogous to a classic problem for Cartesian dualism. The interaction problem concerns how capacities conceived as intrinsically independent of the power of reason can interact with this power in what is intuitively the right way. The unity problem concerns how an additive theorist can explain a rational subject's entitlement to conceive of the animal whose perceptual and desiderative life he or she oversees as 'I' rather than 'it'. I argue that these difficulties motivate a general skepticism about the additive approach, and I sketch an alternative, 'transformative' framework in which to think about the cognitive and practical capacities of a rational animal.